2021
DOI: 10.1186/s40560-021-00551-x
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an artificial intelligence model for intubation difficulty classification by deep learning (convolutional neural network) using face images: an observational study

Abstract: Background Tracheal intubation is the gold standard for securing the airway, and it is not uncommon to encounter intubation difficulties in intensive care units and emergency rooms. Currently, there is a need for an objective measure to assess intubation difficulties in emergency situations by physicians, residents, and paramedics who are unfamiliar with tracheal intubation. Artificial intelligence (AI) is currently used in medical imaging owing to advanced performance. We aimed to create an AI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(52 citation statements)
references
References 28 publications
0
52
0
Order By: Relevance
“…Furthermore, in this case too, models with high sensitivity (90% for BRF) and models with high specificity and accuracy, respectively 91% and 83%, if we consider light gradient boosting machines (LGBM), have been identified. Finally, Hayasaka et al ( 15 ) developed a convolutional neural network (CNN) algorithm capable of evaluating the difficulty of intubation with an excellent AUC of 0.864 just by evaluating patients’ facial pictures, making it a promising tool for predicting these casualties in advice.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in this case too, models with high sensitivity (90% for BRF) and models with high specificity and accuracy, respectively 91% and 83%, if we consider light gradient boosting machines (LGBM), have been identified. Finally, Hayasaka et al ( 15 ) developed a convolutional neural network (CNN) algorithm capable of evaluating the difficulty of intubation with an excellent AUC of 0.864 just by evaluating patients’ facial pictures, making it a promising tool for predicting these casualties in advice.…”
Section: Discussionmentioning
confidence: 99%
“…( 24 ); Studies have also shown that difficult airways can be distinguished from frontal images using depth learning model sets ( 25 ). Likewise, it has been shown that the CNN algorithm can classify difficult airways ( 26 ). Our study is the first to use a large number of machine learning algorithms and deep learning algorithms simultaneously to predict difficult airways in patients with thyroid problems.…”
Section: Discussionmentioning
confidence: 99%
“…The AI model recognized facial contours and then identified expected intubation difficulties, with 80.5% accuracy, 81.8% sensitivity, 83.3% specificity and an AUC of 0.864 (CI 95%, 0.731–0.969). [20]…”
Section: Discussion/observationsmentioning
confidence: 99%
“…The AI model recognized facial contours and then identified expected intubation difficulties, with 80.5% accuracy, 81.8% sensitivity, 83.3% specificity and an AUC of 0.864 (CI 95%, 0.731-0.969). [20] Other studies have approached the role of machine learning as a complement to the physical exam, performing automatic facial analysis and detecting morphological traits related to difficult airways. [21,22] It has also been applied to monitoring pediatric airways, enhancing the detection of critical incidents and providing early warnings to the clinician.…”
Section: Artificial Intelligence In Airway Managementmentioning
confidence: 99%